FUNCTIONAL AND SEMANTIC POTENTIAL OF ACHROMATIC COLORS IN CONTEMPORARY UKRAINIAN POETRY ABOUT WAR - Shytyk, Liudmyla; Yuldasheva, Liudmyla (Linguistic Bulletin (Movoznavchyi Visnyk), 2023)
Introduction. The relevance of the article is determined by the need to investigate the aesthetic and functional-semantic potential of achromatic coloratives in modern war poetry. The analysis of such nominations and the study of the success of the author’s coding of information using the coloratives are important for determining the structure of the artistic text and its interpretation in general. Purpose. The purpose of the article is to research the semantic perspective of the functioning of achromatic coloratives and their symbolic meaning in modern poetic military discourse. Methods. The main methods of research are the method of linguistic description of language facts – for the inventory and systematization of achromatic coloratives; interpretive method – for analyzing the authors’ intentions; method of component analysis – to research the semantics of lexemes. Results. The specifics of the use of achromatic coloratives in poetic texts are analyzed; direct nomination and figurative meaning of coloratives are described; the peculiarities of the use of achromatic colorants are characterized. It was found that coloratives formed under the influence of the traditional meaning of color concepts in the national linguistic picture of the world are at the same time means of individual understanding and aesthetic preferences of the author. Accordingly, coloratives have various connotative shades, which emphasize informative and evaluative functions. Originality. The originality of the scientific research lies in the fact that for the first time the functional and semantic potential of achromatic coloratives in modern war poetry is researched, and their place and role in the organization of the artistic world is characterized. Traditional and new means of poetic expression of the semantics of achromatic colors are analyzed, and the peculiarities of the aesthetic transformation of the semantics of coloratives were researched in the context of poetic military discourse. Conclusion. It was concluded that the connotative semantics of achromatic color names is formed under the influence of the context. Coloratives help to convey the author’s worldview, make it possible to deeply understand the text and shape the recipient’s attitude to the text. The selection of coloratives depends on their semantic structure, and the color system of each writer is formed under the influence of the nationallinguistic and individual-author’s picture of the world. Usually, achromatic coloratives function as components of opposition or as parts of one whole that complement each other. However, the contrasting combination is not limited to the presented colors. The wide lexical-semantic field of coloratives that function in war poetry can become the subject of further research.